Poly(ADP-Ribosyl) Glycohydrolase Prevents the Accumulation of Unusual Replication Structures during Unperturbed S Phase - Ray Chaudhuri, Arnab; Ahuja, Akshay Kumar; Herrador, Raquel; Lopes, Massimo (Molecular and cellular biology, 2015)
Poly(ADP-ribosyl)ation (PAR) has been implicated in various aspects of the cellular response to DNA damage and genome stability. Although 17 human poly(ADP-ribose) polymerase (PARP) genes have been identified, a single poly(ADP-ribosyl) glycohydrolase (PARG) mediates PAR degradation. Here we investigated the role of PARG in the replication of human chromosomes. We show that PARG depletion affects cell proliferation and DNA synthesis, leading to replication-coupled H2AX phosphorylation. Furthermore, PARG depletion or inhibition per se slows down individual replication forks similarly to mild chemotherapeutic treatment. Electron microscopic analysis of replication intermediates reveals marked accumulation of reversed forks and single-stranded DNA (ssDNA) gaps in unperturbed PARG-defective cells. Intriguingly, while we found no physical evidence for chromosomal breakage, PARG-defective cells displayed both ataxia-telangiectasia-mutated (ATM) and ataxia-Rad3-related (ATR) activation, as well as chromatin recruitment of standard double-strand-break-repair factors, such as 53BP1 and RAD51. Overall, these data prove PAR degradation to be essential to promote resumption of replication at endogenous and exogenous lesions, preventing idle recruitment of repair factors to remodeled replication forks. Furthermore, they suggest that fork remodeling and restarting are surprisingly frequent in unperturbed cells and provide a molecular rationale to explore PARG inhibition in cancer chemotherapy.